Response of Saccharomyces cerevisiae var. diastaticus to nerol: Evaluation of antifungal potential by inhibitory effect and proteome analyses. (1st March 2023) - Hong, Kai; Wang, Limin; Johnpaul, Agbaka; Song, Yumei; Guo, Liyun; Xie, Xin; Lv, Chenyan; Ma, Changwei
Highlights: Nerol has antimicrobial effect on S. diastaticus . Nerol inhibits S. diastaticus by damaging membrane integrity. Nerol treatment stimulated yeast cells' detoxification response. Abstract: Saccharomyces cerevisiae var. diastaticus ( S. diastaticus ) is a major spoilage yeast in brewing. In the present research, the antifungal properties of nerol and the proteome response of S. diastaticus were studied. Results showed nerol can inhibit cell budding and delay yeast fermentation in a dose-depended manner. After 3 d of treatment with 0.25 mg·mL −1 nerol, intracellular ROS levels increased 1.66-fold (P < 0.01), and the cells with damaged membrane increased to 23.2 %. Quantitative proteomic profiles utilizing a capillary-HPLC-MS/MS technology revealed that proteins involved in the metabolism of fermentable sugars were up-regulated in S. diastaticus cells treated with nerol, indicating nerol treatment altered the metabolite pattern of fermentable sugars. Proteins associated with the cell membrane biogenesis, heat shock proteins, amino acid biosynthesis, and glutathione metabolism were similarly up-regulated. These findings revealed the mechanism of nerol-induced yeast cell damage as well as the detoxification response of yeast cells.